2015
DOI: 10.1016/j.neuroscience.2015.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Structural imaging of hippocampal subfields in healthy aging and Alzheimer’s disease

Abstract: Hippocampal atrophy, as evidenced using magnetic resonance imaging (MRI), is one of the most validated, easily accessible and widely used biomarkers of Alzheimer's disease (AD). However, its imperfect sensitivity and specificity have highlighted the need to improve the analysis of MRI data. Based on neuropathological data showing a differential vulnerability of hippocampal subfields to AD processes, neuroimaging researchers have tried to capture corresponding morphological changes within the hippocampus. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
273
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(311 citation statements)
references
References 218 publications
(281 reference statements)
32
273
6
Order By: Relevance
“…If individual subfields are differentially vulnerable to age-related change, then averaging activity across regions could produce variable findings. Importantly, research in aged rodents suggests focal changes, indicating selective synaptic weakening among perforant path inputs from ERC to DG and CA3, as well as representational rigidity in CA3 place cells (8,9,11).…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…If individual subfields are differentially vulnerable to age-related change, then averaging activity across regions could produce variable findings. Importantly, research in aged rodents suggests focal changes, indicating selective synaptic weakening among perforant path inputs from ERC to DG and CA3, as well as representational rigidity in CA3 place cells (8,9,11).…”
Section: Significancementioning
confidence: 99%
“…We aimed to determine whether variability in associative memory performance could be explained by variability in a specific combination of structural and functional metrics. Based on prior structural findings, we hypothesized that ERC (15)(16)(17)(18)(19) and CA1-SRLM (11,28) thickness would be positively linked to associative memory performance. Motivated by prior functional findings, we hypothesized that taskrelated activity in DG/CA3 (31,(33)(34)(35) and ERC (36)(37)(38)(39)(40)(41) would be negatively linked to associative memory performance.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…These techniques were applied to a variety of diseases in small single-site studies and usually found subfield volumetry to be superior to standard whole hippocampal volumetry for the detection of hippocampal damage in the early stages of the disease process, for differentiating between diseases or for the investigation of structure/function relationships (e.g., Wang et al, 2006;Ballmaier et al, 2008;Mueller et al, 2008;Schobel et al, 2009;Neylan et al, 2010;Bender et al, 2013;Kerchner et al, 2014;SchoeneBake et al, 2014;Chao et al, 2014;Hsu et al, 2015;De Flores et al, 2015;Pluta et al, 2012;Yushkevich et al, 2015b). The promise of hippocampal subfield volumetry techniques however led to two unexpected developments that could potentially limit the usefulness of this approach.…”
Section: Introductionmentioning
confidence: 99%